2020
DOI: 10.1088/2515-7655/abd385
|View full text |Cite
|
Sign up to set email alerts
|

Ready-to-use paper biofuel cell driven by water

Abstract: A biofuel cell that can generate electricity using only water is expected to be used as a new energy harvester for an emergency power supply. A new 4-series/4-parallel structured paper-substrate biofuel cell was prepared using a fuel supply paper preloaded with glucose and phosphate buffer salts. When a power generation test was conducted by supplying water to the fuel-preloaded paper, the paper-based biofuel cell produced an output approximately 90% (0.84 mW) of that obtained by supplying a phosphate buffer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For instance, Selvarajan et al 127 created a PENG-driven cysteine sensor by functionalizing BaTiO 3 nanoparticles and agarose, which had a linear range of detection of ∼10 μM cysteine. Additionally, aiming to provide energy to biochemical sensors, Shitanda et al 192 developed a paper-based biofuel cell, which showed an output of about 0.84 mW when water was added and V oc is 2.1 V, which has potential applications in nappy BFC-type urine timing sensors for non-diabetic patients.…”
Section: Urine Monitoringmentioning
confidence: 99%
“…For instance, Selvarajan et al 127 created a PENG-driven cysteine sensor by functionalizing BaTiO 3 nanoparticles and agarose, which had a linear range of detection of ∼10 μM cysteine. Additionally, aiming to provide energy to biochemical sensors, Shitanda et al 192 developed a paper-based biofuel cell, which showed an output of about 0.84 mW when water was added and V oc is 2.1 V, which has potential applications in nappy BFC-type urine timing sensors for non-diabetic patients.…”
Section: Urine Monitoringmentioning
confidence: 99%
“…As a result, EBFCs provide the basis for the fabrication of energy conversion devices with a power output proportional to the conversion at the limiting electrode. Hence, they have gained considerable attention for their utilization in point‐of‐care diagnosis, self‐powered biosensors, and implantable devices as well as wearable and portable power supplies [7–13].…”
Section: Introductionmentioning
confidence: 99%